The Role of Regional Taxes in Improving the Quality of Public Infrastructure in DKI Jakarta - Dewi, Siti Rachmi; Inayati, Inayati (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2024)
This study aims to understand the role of local taxes in supporting public infrastructure development in DKI Jakarta and to reveal factors that influence public awareness, compliance, and expectations regarding tax management. Using a post-positivism paradigm with a qualitative approach, data were collected through document analysis and in-depth interviews with purposively selected communities. Thematic analysis methods were applied to identify key themes in three main dimensions: experience of paying local taxes, experience of using public infrastructure, and expectations regarding local tax policies. The results of the study show that although public awareness of the urgency of taxes for infrastructure development is relatively high, the level of compliance is still not optimal. One digital service such as Samsat Digital Nasional (SIGNAL) has succeeded in increasing the ease of payment, but various obstacles including digital literacy, limited internet infrastructure, and lack of socialization limit its use. On the other hand, the public appreciates major projects such as mass transportation and main roads, but still complains about the inequality of infrastructure in the suburbs and the problem of flooding. Public expectations regarding local tax policies emphasize the importance of transparency, accountability, and public participation in formulating development priorities. These findings emphasize the need for a comprehensive strategy to bridge the gap between awareness of the importance of taxes and factual compliance in paying taxes. Local governments are advised to strengthen the socialization of digital services, prioritize equal distribution of infrastructure, and implement an interactive financial reporting system to build public trust and participation in a sustainable manner. Thus, the capacity of public infrastructure funding through local taxes can continue to be increased, in line with efforts to realize public welfare in the DKI Jakarta Province.